2020
DOI: 10.1186/s43170-020-00002-x
|View full text |Cite|
|
Sign up to set email alerts
|

Endophytic colonization of tomato plants by the entomopathogenic fungus Beauveria bassiana for controlling the South American tomato pinworm, Tuta absoluta

Abstract: Background: The deployment of entomopathogenic fungi (EPF) for the control of crop pests is an important alternative to synthetic pesticides. Despite recent advances in EPF formulations and application techniques, their efficacy is still limited by abiotic and biotic factors. Entomopathogenic fungi naturally colonize plant tissues or they can be artificially inoculated, protecting the plants from insect attack. Beauveria bassiana is the most widely used fungal biological control agent and has potential as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
(66 reference statements)
2
32
0
Order By: Relevance
“…Barra-Bucarei et al (2020) state that endophytic fungal isolates have the ability to have a systemic mode of action. The results of detection by Carolina et al (2020) show that the endophytic fungi can still be found in the roots, stems and leaves up to 30 days after inoculation. However, according to Shikano (2018), the endophytic fungi are able to colonize plant parts for several months and the duration of their persistence in the plant tissue varies depending on the age of the plant (high persistence in young tissues).…”
Section: Discussionmentioning
confidence: 96%
“…Barra-Bucarei et al (2020) state that endophytic fungal isolates have the ability to have a systemic mode of action. The results of detection by Carolina et al (2020) show that the endophytic fungi can still be found in the roots, stems and leaves up to 30 days after inoculation. However, according to Shikano (2018), the endophytic fungi are able to colonize plant parts for several months and the duration of their persistence in the plant tissue varies depending on the age of the plant (high persistence in young tissues).…”
Section: Discussionmentioning
confidence: 96%
“…These entomopathogenic fungal strains recovered from different parts of tomato plant tissues (roots, stems, and leaves) that con rmed their potential to move and establish throughout the plant parts. The entophytic colonization of tomato (Mwamburi, 2021;Silva et al, 2020), soybean (Russo et al, 2019), pecan (Ramakuwela et al, 2020), and coconut (Gaviria et al, 2020) have been achieved by both B. bassiana and M. anisopliae strains. This suggests that these entomopathogenic fungal isolates have the potential to colonize different plant species besides to tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato plant tissues have been naturally and arti cially colonized with entomopathogenic fungi and they can promote growth and protect plants from insect pests (Silva et al, 2020). According to (Barra-Bucarei et al, 2020), the endophytic B. bassiana has the potential to control T. vaporariorum and promote the growth of tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…The most bacterial control agents used to manage T. absoluta is Bacillus thuringiensis, [29,30,31,32] and Saccharopolyspora spinosa [33] . Also, several entomopathogenic fungi are used in the control of tomato leaf miner: Metarhizium anisopliae [34,35] ; Beauveria bassiana [36,37,38] , Aspergillus oryzae [39] , Saria farinosa [40] , Clonostachys sp [38] and Purpureocillium lilacinum [40] . Nutrient exhaustion and toxicosis induced by fungi penetration leads to death of the insect [41] .…”
Section: Bacteria and Entomopathogenic Fungimentioning
confidence: 99%